Determination of Procalcitonin Levels in Patients with Nephropathia Epidemica - A Useful Tool or an Unnecessary Diagnostic Procedure? - Joerg Latus; Daniel Kitterer; Stephan Segerer; Ferruh Artunc; M. Dominik Alscher; Niko Braun (Karger Publishers, 2015)
Background/Aims: Puumala virus causes nephropathia epidemica (NE), a milder form of hemorrhagic fever with renal syndrome that occurs in Central and Northern Europe. Several studies have sought to identify risk factors for severe NE. However, elevated procalcitonin (PCT) levels have not previously been investigated as a predictive marker for a severe course of NE. Methods: A cross-sectional prospective survey of 456 adults with serologically confirmed NE was performed. Results: PCT levels at the time of diagnosis were available for 43 out of 456 patients, and in 24 of these patients (56%) PCT levels were elevated ("PCT positive"). C-reactive protein (CRP) levels at admission to hospital and peak CRP levels during the acute course of the disease were higher in the PCT-positive compared with the PCT-negative group (pConclusions: Elevated PCT levels are common in patients with acute NE. There was no association between PCT levels and severity of disease, including AKI or thrombocytopenia. It is important to distinguish Puumala virus infection from other causes of AKI with thrombocytopenia. However, PCT might not be useful in differentiating hantavirus infection from bacterial infection.